THE EFFECT OF THE UNPLOYMENT RATE AND MINIMUM WAGE ON POVERTY RATE IN WEST JAVA - Assyifa Putri Syauqiah; Koresy Wilma Pattiasina; Salsabilla Firdausyah (Lembaga Penerbit Fakultas EKonomi dan Bisnis, 2022)
This study aims to determine the analysis of the effect of the unemployment rate and minimum wage on the poverty rate in the province of West Java in 2015 – 2019. This type of research uses quantitative data analysis. The data used in this study is secondary data obtained from the Central Statistics Agency (BPS). The secondary data used in this study is panel data that uses a combination of time series (time series) from 2015 - 2019 and a cross section of 6 cities in West Java Province and succeeded in producing 30 observations. Panel Data Regression Calculation using Eviews 9 software. The results of the study indicate that the Unemployment Rate has a positive and insignificant effect on the Poverty Level in the province of West Java. It can be seen from the results where the coefficient value is 0.016342 with a probability value of 0.9232 > 0.05. The Minimum Wage has a negative and significant effect on the Poverty Level in the province of West Java. It can be seen from the results of data processing where the coefficient value is - 1.472288 and the probability value is 0.0000 < 0.05. The panel regression equation is known to have a constant of 9.807146, the Unemployment Rate and Minimum Wage Variables have an effect on the Poverty Level with a probability value of F-statistics 0.0000 < 0.05, and the coefficient of determination (R2) is 0.980167. That is, the independent variable (Unemployment Rate and Minimum Wage) is able to explain the dependent variable (Poverty Level) of 98.01% and the remaining 1.99% is explained by other variables outside the model.